Prevalence of Trypanosoma evansi infections in buffaloes, beef and dairy cattle in Sakon Nakhon province using molecular and serological assays - Suwan, Eukote; Chalermwong, Piangjai; Choocherd, Suchada; Wichainchot, Sakulchit; Thabthimsri, Chanapath; Saengsawang, Phirabhat; Desquesnes, Marc; Wanwisa wachoom,; Wongpanit, Kannika; Jittapalapong, Sathaporn (Agriculture and Natural Resources, 2023)
Importance of the work: Trypanosoma evansi is a vector-borne pathogen, responsible for T. evansi infection (surra) which has a major impact on animal health in Southeast Asia, including Thailand. Objectives: To update the current situation regarding trypanosome infections of cattle and buffaloes in Sakon Nakhon province, Thailand. Materials & Methods: Blood samples were collected from buffaloes (455) and beef (1,077) and dairy (227) cattle in eight districts of Sakon Nakhon province and tested for trypanosome infections using T. evansi indirect-enzyme-linked immunosorbent assay (ELISA) and TRYP1 polymerase chain reaction (PCR). Results: Among the 1,759 samples, there were 77 positives (4.38%; 77/1,759) from T. evansi indirect-ELISA and 8 positives (0.45%; 8/1,759) from TRYP1 PCR, of which two samples were positives for both tests. The ITS1 sequencing analysis revealed high T. evansi sequence identities (97.22–100%). Factors associated with T. evansi infections were age, species, farm size and district. The highest prevalence was in buffaloes (9.67%; 44/455), followed by beef cattle (3.25%; 35/1,077) and dairy cattle (1.76%; 4/227). The significant associations with T. evansi infection were an animal age of 1–3 yr (6.82%; 53/777; p = 0.00), a medium herd size (5.99%; 13/217; p = 0.03) and farm located in Phanna Nikhom district (21.33%; 32/150; p = 0.00). Main finding: Cattle and buffaloes in Sakon Nakhon province had a low prevalence (less than 5%) for current infection by T. evansi. However, the prevalence of trypanosome infections might be increasing due to the high densities of blood-sucking flies.